A phenotypic risk score for predicting mortality in sickle cell disease. (28th January 2021) - Sachdev, Vandana; Tian, Xin; Gu, Yuan; Nichols, James; Sidenko, Stanislav; Li, Wen; Beri, Andrea; Layne, W. Austin; Allen, Darlene; Wu, Colin O.; Thein, Swee Lay
Summary: Risk assessment for patients with sickle cell disease (SCD) remains challenging as it depends on an individual physician's experience and ability to integrate a variety of test results. We aimed to provide a new risk score that combines clinical, laboratory, and imaging data. In a prospective cohort of 600 adult patients with SCD, we assessed the relationship of 70 baseline covariates to all‐cause mortality. Random survival forest and regularised Cox regression machine learning (ML) methods were used to select top predictors. Multivariable models and a risk score were developed and internally validated. Over a median follow‐up of 4·3 years, 131 deaths were recorded. Multivariable models were developed using nine independent predictors of mortality: tricuspid regurgitant velocity, estimated right atrial pressure, mitral E velocity, left ventricular septal thickness, body mass index, blood urea nitrogen, alkaline phosphatase, heart rate and age. Our prognostic risk score had superior performance with a bias‐corrected C‐statistic of 0·763. Our model stratified patients into four groups with significantly different 4‐year mortality rates (3%, 11%, 35% and 75% respectively). Using readily available variables from patients with SCD, we applied ML techniques to develop and validate a mortality risk scoring method that reflects the summation of cardiopulmonary, renal and liver end‐organ damage. Trial Registration: ClinicalTrials.gov Identifier: NCT#00011648.